An approach to measuring the perception of teen parenting practices - Flores Galaz , Mirta Margarita (Consorcio de Universidades Mexicanas A.C., 2016)
This study aimed to construct and validate a scale to measure the perception of parenting for Mexican adolescents. A total of 432 teenagers were selected through a no probabilistic sampling from six states in Mexico: 180 (60 each one) from Sonora, Toluca and Hidalgo; 100 from Zacatecas, 103 from Yucatan and 49 of Coahuila. 187 were women and 185 men (60 persons did not indicate their sex). The average age was 14.15 years with a standard deviation of 1.28. The Perceived of Parenting Practices for Adolescents consists of 63 claims in a 5-point Likert-style scale (1= Never, to 5 = Always) that assess the perceived frequency of activities than father and mother do every day to educate them according to the adolescents. Results, obtained through the exploratory factor analysis, showed that for the Mom subscale four factors were formed: Care and warmth (alpha = 0.93), Transmission of values (alpha = 0.83), Support and school guidance (alpha = 0.73) and Behavioral control (alpha = 0.57). The Dad subscale was form by seven factors although only five showed conceptual consistency: Care and warmth (alpha 0.95), Transmission of values (alpha = 0.73), Inductive discipline (alpha = 0.70), School support and guidance (alpha = 0.72), Behavioral control (alpha = 0.57). Psychometric properties of the instrument were analized and differences between criterion variables (sex and geographic zone).